Homocisteína e fatores de risco cardiovascular em crianças e adolescentes - Leal, Adriana Amorim de Farias (2013)
Objective: Study the relationship between homocysteine (Hy) and cardiovascular risk factors in overweight or obese children and adolescents. Material and Methods: Article 1 - Were performed a systematic review of literature, and screened studies published between 1997 and 2011 about Hy and cardiovascular risk in childhood, in the databases LILACS, IBECS, Science Direct, Medline and Cochrane. Article 2 - Was developed a cross-sectional study was conducted with children and adolescents overweight or obese, seen at center Childhood Obesity, in Campina Grande-PB, from July 2011 to May 2012. The association between Hy and other cardiovascular risk factors were evaluated using the chi-square test and comparison of Hy means was conducted by analysis of variance, using a 5% of significance. Results: In the systematic review were analyzed 15 articles that pointed direct relation between plasma levels of Hy and males (ten studies) and with increasing age (eight studies), and an inverse relation with blood levels of B6, B12 and folate vitamins (ten studies ). In the second article were evaluated 165 children and adolescents with a mean age of 12.5 (± 3.5) years, of which 24,2% had elevated levels of Hy. The Hy means was higher in patients with insulin resistance (10,0 μmol/L). Conclusions: This research reinforces the importance of study emerging cardiovascular risk factors, such as the Hy, to guide prevention and / or treatment of obesity and cardiovascular diseases.